A Reduction in Time with Electronic Monitoring In Stroke (ARTEMIS): study protocol for a randomised multicentre trial. Issue 6 (27th June 2018) - Koster, Gaia T; Nguyen, T Truc My; Groot, Adrien E D; Coutinho, Jonathan M; Bosch, Jan; den Hertog, Heleen M; van Walderveen, Marianne A A; Algra, Ale; Wermer, Marieke J H; Roos, Yvo B; Kruyt, Nyika D
Abstract : Introduction: Time is the most crucial factor limiting efficacy of intravenous thrombolysis (IVT) and intra-arterial thrombectomy (IAT). The delay between alarming the Emergency Medical Services (EMS) dispatch office and IVT/IAT initiation, that is, the 'total system delay' (TSD), depends on logistics and team effort. A promising method to reduce TSD is real-time audio-visual feedback to caregivers involved. With 'A Reduction in Time with Electronic Monitoring in Stroke' (ARTEMIS), we aim to investigate the effect of real-time audio-visual feedback on actual TSD to IVT/IAT to caregivers. Methods and analysis: ARTEMIS is a multiregional, multicentre, randomised open end-point trial including patients ≥18 years considered IVT/IAT-eligible by the EMS dispatch office or on-site EMS personnel. Patients are electronically tracked and randomised for real-time audio-visual feedback on TSD to caregivers via premounted handhelds and tablets throughout the TSD trajectory. Primary outcome is TSD to IVT/IAT. Secondary outcomes comprise proportion of IVT/IAT-treated patients, symptomatic intracerebral haemorrhage, IVT/IAT-treated stroke mimics, clinical outcome after three months and cost-effectiveness. Separate analyses for IAT-patients with or without prior IVT, within or out of office hours and EMS region will be performed. With 75 IAT-patients and 225 IVT-patients in each arm, we will be able to demonstrate a 20 min difference in TSD to IAT and a 10 min difference in TSD to IVT (p=0.05 and power=0.8). Ethics and dissemination: Study findings will be disseminated through peer-reviewed journals and (inter)national conference presentations. Trial registration number: NCT02808806; Pre-results.